Game-related performance factors in four European men`s professional volleyball championships - Pena, J.; Casals, M. (Journal of Human Kinetics, 2016)
The present study was designed to assess the relevance of game-related performance factors as outcome predictors in high-level volleyball. To carry out the analysis, the official box scores of 399 matches played by 47 different teams in four different European male professional volleyball leagues (Italy, Poland, Germany and Turkey) during the 2013-14 regular season were analyzed. A logistic mixed model was performed to determine the effects of different variables in matches` outcomes. According to the multivariate analysis the following factors were significantly associated with winning matches: the number of scorers (OR = 1.32; CI: 1.09 - 1.59), service errors (OR = 0.91; CI: 0.87 - 0.95), service points (OR = 1.25; CI: 1.15 -1.36), reception errors (OR = 0.79; CI: 0.74 - 0.84), the percentage of positive receptions (OR = 1.02; CI: 1.00 -1.04) and blocked balls (OR = 1.17; CI: 1.11 - 1.26). Team category 2 (OR = 0.39; CI: 0.24 - 0.63) and team category 3 (OR = 0.15; CI: 0.09 - 0.25) were significantly associated with losing matches. These findings can contribute to a better understanding of performance indicators in professional volleyball, helping coaches and decision makers to better determine the importance of particular game factors.